The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.bbrc.2016.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Myomir dysregulation and reactive oxygen species in aged human satellite cells

Abstract: Satellite cells that reside on the myofibre surface are crucial for the muscle homeostasis and regeneration. Aging goes along with a less effective regeneration of skeletal muscle tissue mainly due to the decreased myogenic capability of satellite cells. This phenomenon impedes proper maintenance and contributes to the age-associated decline in muscle mass, known as sarcopenia. The myogenic potential impairment does not depend on a reduced myogenic cell number, but mainly on their difficulty to complete a diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 37 publications
4
47
0
1
Order By: Relevance
“…Aging is associated with high levels of muscle ROS in vivo , which may contribute to increased apoptosis and cell death and reduced myoblast differentiation leading to poor muscle repair [20]. High levels of ROS are associated with metabolic diseases like diabetes [16,20,36], which may contribute to the loss of myoblast function, increase myoblast cell death [33] and further exacerbate muscle repair in aging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging is associated with high levels of muscle ROS in vivo , which may contribute to increased apoptosis and cell death and reduced myoblast differentiation leading to poor muscle repair [20]. High levels of ROS are associated with metabolic diseases like diabetes [16,20,36], which may contribute to the loss of myoblast function, increase myoblast cell death [33] and further exacerbate muscle repair in aging.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of ROS are associated with metabolic diseases like diabetes [16,20,36], which may contribute to the loss of myoblast function, increase myoblast cell death [33] and further exacerbate muscle repair in aging. Fulle and colleagues [25] have demonstrated that a high percentage of the myogenic precursor cells from elderly muscles undergo apoptosis triggered by mitochondrial-associated caspase-9 and this appears to be closely linked to the high ROS levels that are found in aged muscles [20]. Thus, we predict that strategies to attenuate high ROS levels should reduce apoptosis in myoblasts and improve muscle differentiation/repair in aging and in other diseases that have elevated ROS levels.…”
Section: Introductionmentioning
confidence: 99%
“…The process of skeletal muscle differentiation is governed at least in part by miR-1, miR-206, and miR-133, which regulate the expression of MRF-encoding genes such as MyoD, Myogenin, and Mef2 [31]. Indeed, microRNAs are important regulators involved in the establishment and maintenance of skeletal muscle differentiation [22,[32][33][34]. For example, it was demonstrated that the expression of both miR-1 and miR-133 was enriched in striated muscle, and the differentiated myoblasts showed an elevated expression of miR-1 and miR-133 [32].…”
Section: Discussionmentioning
confidence: 99%
“…RNA was extracted with Purelink RNA Mini Kits (Invitrogen, Life Technologies, Waltham, MA, USA), and genomic DNA traces were removed with Turbo DNase (Invitrogen, Life Technologies, Waltham, MA, USA), following the manufacturer's instructions. A qRT-PCR was performed on mESCs as described in [34]. The values represent the mean ± SD of three independent experiments performed in triplicate.…”
Section: Rna Extraction and Quantitative Real-time Pcr Analysismentioning
confidence: 99%
“…Os miRNAs conhecidos como músculo-especificos foram descritos como participantes principalmente dos processos de proliferação de células satélite, miogênese e hipertrofia muscular, são eles, miR-1, miR-133a, miR-133b, miR-206, miR-208b, miR-486 e miR-499, os quais estão presentes nos músculos esquelético e cardiaco (Di Filippo et al, 2016;Horak et al, 2016;Van Rooij et al, 2008). Além disso, diversos estudos têm relatado outros miRNAs envolvidos na miogênese, como por exemplo, miR-26 na diferenciação de mioblastos (Dey et al, 2012), miR-128 na inibição de proliferação de mioblastos (Motohashi et al, 2013), e miR-489 na manutenção do estado de quiescência das células satélite (Cheung et al, 2012).…”
Section: Micrornas No Músculo Esqueléticounclassified